1997
DOI: 10.2500/105065897781446784
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up of University of Virginia Experience with the Modified Lothrop Procedure

Abstract: Current surgical treatment of the frontal sinus disease include external approaches to obliterate or ablate the sinus and both external and transnasal methods to restore drainage into the nasal cavity. The original Lothrop procedure resects the medial frontal sinus floor, superior nasal septum, and intersinus septum, creating a large frontonasal communication. However, as described, the external approach used in this procedure often allowed medial collapse of soft tissue and the stenosis of the nasofrontal com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 11 publications
0
51
0
3
Order By: Relevance
“…6,10-12 These studies are case series with multiple independent arms or independent cohorts compared over time. In a study by Gross et al, 10 Copyright (c) Oceanside Publications, Inc. All rights reserved. For permission to copy go to https://www.oceansidepubl.com/permission.htm time periods.…”
Section: Resultsmentioning
confidence: 95%
“…6,10-12 These studies are case series with multiple independent arms or independent cohorts compared over time. In a study by Gross et al, 10 Copyright (c) Oceanside Publications, Inc. All rights reserved. For permission to copy go to https://www.oceansidepubl.com/permission.htm time periods.…”
Section: Resultsmentioning
confidence: 95%
“…Gross et al reported the cost advantage of the endoscopic modified Lothrop procedure over the frontal osteoplastic flap procedure with obliteration. 11 However, unlike the frontal osteoplastic flap procedure with obliteration, patients who undergo an endoscopic modified Lothrop procedure require frequent postoperative clinic visits to ensure patency of the frontal sinus opening, with toileting of the frontal sinus cavity to remove clots, crust, polyps and/or granulation. The additional cost of these clinic visits was not included in Gross and colleagues' cost analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Other complications reported for the endoscopic modified Lothrop procedure include transient blurring of vision, which in one study resolved spontaneously by post-operative day one 11. …”
mentioning
confidence: 95%
“…The literature on Draf III frontal sinusotomies is similar to that on the Draf IIa consisting predominantly of case series from single institutions (Table 3) 24,26,39,4161 with similar outcomes. In some ways, though, more evidence has been published on this salvage surgery that is required in only a minority of patients with CRS.…”
Section: Introductionmentioning
confidence: 88%
“… LOE = level of evidence, RCS = retrospective case series, OPF = osteoplastic flap, * endpoint reported is endoscopic closure, not revision surgery Data from Refs 24,39,26,4161. …”
Section: Tablementioning
confidence: 99%